Sled-Push Load-Velocity Profiling and Implications for Sprint Training Prescription in Young Athletes. Issue 11 (November 2021) - Cahill, Micheál J.; Oliver, Jon L.; Cronin, John B.; Clark, Kenneth P.; Cross, Matt R.; Lloyd, Rhodri S.
Abstract : Abstract: Cahill, MJ, Oliver, JL, Cronin, JB, Clark, KP, Cross, MR, and Lloyd, RS. Sled-push load-velocity profiling and implications for sprint training prescription in young athletes. J Strength Cond Res 35(11): 3084–3089, 2021—Resisted sled pushing is a popular method of sprint-specific training; however, little evidence exists to support the prescription of resistive loads in young athletes. The purpose of this study was to determine the reliability and linearity of the force-velocity relationship during sled pushing, as well as the amount of between-athlete variation in the load required to cause a decrement in maximal velocity (Vdec) of 25, 50, and 75%. Ninety ( n = 90) high school, male athletes (age 16.9 ± 0.9 years) were recruited for the study. All subjects performed 1 unresisted and 3 sled-push sprints with increasing resistance. Maximal velocity was measured with a radar gun during each sprint and the load-velocity (LV) relationship established for each subject. A subset of 16 subjects examined the reliability of sled pushing on 3 separate occasions. For all individual subjects, the LV relationship was highly linear ( r > 0.96). The slope of the LV relationship was found to be reliable (coefficient of variation [CV] = 3.1%), with the loads that cause a decrement in velocity of 25, 50, and 75% also found to be reliable (CVs = <5%). However, there was large between-subject variation (95% confidence interval) in the load that caused a given Vdec, with loads of 23–42% body mass (%BM) causing a Vdec of 25%, 45–85 %BM causing a Vdec of 50%, and 69–131 %BM causing a Vdec of 75%. The Vdec method can be reliably used to prescribe sled-push loads in young athletes, but practitioners should be aware that the load required to cause a given Vdec is highly individualized.